Monocyte clusters suggestive of a chronic inflammatory phenotype are associated with reduced endothelial function in Veterans with respiratory symptoms - Gregory Pappas; Carol Gardner; Changjiang Guo; Kathleen Black; Raymond Rancourt; Debra Laskin; Howard Kipen; Anays Sotolongo; Michael Falvo; Andrew Gow (PLoS ONE, 2026)
Exposure to airborne hazards during deployment is associated with persistent respiratory symptoms among military veterans even years after deployment. Circulating monocytes, key components of the innate immune response, are implicated in inflammatory processes that may be sustained long after such exposures and contribute to related health issues. This cross-sectional study, conducted years after deployment, aimed to characterize monocyte activation profiles in veterans with deployment-related respiratory symptoms and investigate associations with physiological markers of pulmonary and vascular function. Circulating monocyte immunophenotype, pulmonary function, and brachial artery flow-mediated dilation (FMD) were assessed in 82 previously deployed veterans. Using principal component and hierarchical clustering analyses, we identified two distinct monocyte activation phenotypes: Cluster 1, characterized by elevated CD87, CD11b, and CD163, and cluster 2 which expressed markers of non-classical monocytes and CD195, indicative of a chronic inflammatory phenotype. Veterans in cluster 2 exhibited impaired endothelial-dependent vasodilation (FMD/NMD ratio; p = 0.02) and elevated airway resistance (R5; p = 0.01), despite normal pulmonary function. These findings suggest an association between distinct monocyte activation profiles and measures of microvascular and airway dysfunction in this cohort, potentially reflecting sustained inflammation secondary to environmental exposure. These observed associations underscore the need for further research into the role of monocytes in these long-term physiological changes. Elucidating the mechanistic pathways by which these monocyte phenotypes may contribute to persistent physiological alterations is critical and could inform future strategies for identifying at-risk veterans or exploring novel immunomodulatory approaches if such links are further substantiated.